Preventing Water Crisis Through Local Wisdom Larung Sesaji in Sesaji in Siman, Kediri - Nurhairunnisa, Nurhairunnisa (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2024)
This qualitative research aims to analyze how the local practice of the Siman community in Kediri, called Larung sesaji becomes an instrument for maintaining and conserving the existence of water sources in Siman reservoir. Larung sesaji or Larungan is a series of rituals performed by the community every month of suro’ and Hindu melasti celebrations. The locals believe that these activities represent a form of sacrifice to the ancestral spirit so that, the ancestors will preserve nature and water availability in Siman. The research uses qualitative methods including interviews, documentation, data processing, and conclusions. Local community conservation theory of anthropologists Thomas Reuter and E.B. Tylor became an analytical point in the scope of environmental anthropology. The results showed that; [1], the tradition of the local community (Simanes) strongly relates to conservation issues. [2], Larungan became a conservation method to maintain the water crisis in Siman, and this local wisdom continues to this day